Measuring Professional Ethics in Coaching: Development of the PISC-Q. Issue 6 (17th August 2016) - Thompson, Melissa; Dieffenbach, Kristen
Abstract : Sport is commonly lauded as the ideal place for participants to learn life skills. However, concerns related to the "win-centered" sport culture has spurred research into ethical behaviors in sport. The purpose of the present study was to create a measure of professional ethics in coaching. Students enrolled in a collegiate coaching education course ( N = 766) responded to a series of vignettes related to common situations in the coaching profession. Results indicate the Professional Issues in Sport Coaching Questionnaire is an acceptable measure of situation specific professional ethics. Conclusions and directions for future research are discussed.